Estudo morfológico e composicional através de microscopia eletrônica de varredura (MEV) - catodoluminescência (CL) de cristais de zircão dos granitos Seringa e São João, sudeste do Pará: implicações metalogenéticas - SOTÉRO, Aldemir de Melo (2019)
The Seringa and São João granites are anorogenic paleoproterozoic batholiths, with ages of 1895 ± 1 Ma and 1890 ± 2 Ma, respectively, located in the Água Azul do Norte-PA region, southeastern Amazonian Craton. They are intrusive in Archean rocks of the Rio Maria Granite-Greenstone Terrain (Mineral Province of Carajás (CMP). They are formed mainly by rocks of monzogranite and syenogranite compositions, consisting mainly of quartz, alkali-feldspar and plagioclase; biotite and amphibole are varietals minerals and zircon, apatite, allanite and opaque minerals the accessory phases. Morphological and compositional study of zircon of these granites by Scanning Electron Microscopy (SEM), cathodoluminescence (CL) and Energy Dispersive Spectrometry (EDS) semi-quantitative analyses allowed characterize zircons of its different petrographic facies, carry out geochemical comparisons between its zircons and with zircons of other anorogenic granites of the Amazonian craton (Jamon, Velho Guilherme and Serra dos Carajás suites), and comment about metallogenic character of these granites, particularly about associated tin- mineralization. The CL images showed that zircons of Seringa and São João granites are dominantly euhedral to subhedral, strongly zoned and with sizes between 200 and 400 μm. Their cores range from dark to luminescent, sometimes displaying metamictic aspects. Inclusions of apatite truncating or accompanying crystal growth zones are common. Nb an Hf trace elements in the studied zircons has small variations, even in the different facies of the two granites. However, the contents of Nb are more elevated in relation to zircons of other anorogenic granites of the CMP. The zircons of Seringa and São João granites have low contents of Hf and elevated Zr/Hf ratios when compared with zircons of tin-specialized granites of the Velho Guilherme suite, suggesting that they have low potential to tin-mineralization.